Mitigating the Respiratory Health Impacts of Air Pollution on Urban Youth: An Analysis of Policy, Community and Individual Protective Responses - Hai Binh Nguyen; Minh Chinh Pham (International Journal of Public Health and Nursing, 2026)
Air pollution is an increasingly consequential environmental health risk for young people in rapidly urbanizing areas. Yet respiratory risk is shaped not only by pollutant exposure but also by policy effectiveness, community support and individual protective behaviour. This study develops and tests a multilevel framework integrating air-pollution exposure, policy management and control, community action, youth protective awareness and respiratory health symptoms. The original dataset contained 438 questionnaire records. Following screening for substantial non-response and straight-line answering, 421 cases were retained for partial least squares structural equation modelling. The measurement model achieved acceptable internal consistency and convergent validity: Cronbach’s alpha ranged from 0.785 to 0.822, composite reliability from 0.854 to 0.876, and average variance extracted from 0.540 to 0.586. Air-pollution exposure significantly increased respiratory symptoms (β = 0.324, p < 0.001). Policy management strengthened community action, while policy management, community support and perceived exposure promoted youth protective behaviour. However, policy, community and individual protective constructs did not directly reduce respiratory symptoms. The findings indicate that awareness and personal precautions cannot substitute for source-oriented emission control. An integrated intervention architecture is proposed, combining enforceable urban regulation, school- and community-based risk communication, real-time air-quality information and practical exposure-reduction measures.